Persistence of chiseling effects on the compaction of a Nitisol under no‑till in a humid subtropical region - Nunes, Márcio Renato; Pauletto, Eloy Antonio; Denardin, José Eloir; Faganello, Antonio; Pinto, Luiz Fernando Spinelli; Scheunemann, Tiago (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the persistence of chiseling effects on the compaction of a Ferralic Nitisol (Rhodic), under no‑till (NT), in the Brazilian humid subtropical region. The experiment was carried out in randomized complete blocks, with four replicates and six treatments, consisting of the time that the soil was kept under NT after chiseling: continuous NT for 24 months, after chiseling in September 2009; continuous NT for 18 months, after chiseling in March 2010; continuous NT for 12 months, after chiseling in September 2010; continuous NT for six months, after chiseling in March 2011; crop planted right after soil chiseling, in September 2011; and continuous NT, without chiseling (control). The species cultivated in the area were: corn in the 2009/2010 growing season; wheat in 2010; soybean in the 2010/2011 growing season; rye in 2011; and corn in the 2011/2012 growing season. Treatment effects were assessed by soil physical parameters and by morphological and productive parameters of the corn crop in the 2011/2012 growing season. The chiseling of Nitisol under no‑till in a humid subtropical region does not increase corn grain yield, and its effects on soil structure do not last longer than 18 months.